2015
DOI: 10.1007/s11760-015-0810-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated facial expression recognition based on histograms of oriented gradient feature vector differences

Abstract: This article proposes an efficient automated method for facial expression recognition based on the histogram of oriented gradient (HOG) descriptor. This subjectindependent method was designed for recognizing six prototyping emotions. It recognizes emotions by calculating differences on a level of feature descriptors between a neutral expression and a peak expression of an observed person. The parameters for the HOG descriptor were determined by using a genetic algorithm. Support vector machines (SVM) were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 34 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…It is evident from the table that the proposed system leads to achieving the highest classification accuracy compared to all others over both datasets such as CK+ and JAFFE. It can also be observed that Siddiqi et al [15] and Mlakar and Potocinik [6] achieved comparable results on CK+ dataset. Further, a better performance was attained on JAFFE dataset by Zhang and Tjondronegoro [7], Hu et al [30], and Siddiqi et al [15].…”
Section: Comparison With Other Classification Methodsmentioning
confidence: 56%
See 2 more Smart Citations
“…It is evident from the table that the proposed system leads to achieving the highest classification accuracy compared to all others over both datasets such as CK+ and JAFFE. It can also be observed that Siddiqi et al [15] and Mlakar and Potocinik [6] achieved comparable results on CK+ dataset. Further, a better performance was attained on JAFFE dataset by Zhang and Tjondronegoro [7], Hu et al [30], and Siddiqi et al [15].…”
Section: Comparison With Other Classification Methodsmentioning
confidence: 56%
“…The grid search technique has been served as the conventional procedure for obtaining the best results despite it possessing limitations like high computational burden and getting stuck at local minima. Recently, it has been observed that the optimisation methods such as moth‐flame optimisation (MFO) algorithm [43] and genetic algorithm (GA) [6] are widely used to obtain the global best solution as compared to the grid‐search method. Therefore, in this study, the simplest and yet effective optimisation technique, Jaya, is introduced to identify the parameters of RBF based LS‐SVM, and the resultant model is referred to as JOLS‐SVM that is used to predict the emotion class.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…e results indicate that the fear expression misclassified either as anger or disgust emotion. e reason is that the fear, disgust, and anger expressions demonstrated similar muscle activities [37]. Moreover, it is also observed that the average recognition accuracy rate of the CK+ dataset is slightly higher than the MMI dataset.…”
Section: Experiments On MMI Ck+ and Sfew Databasementioning
confidence: 88%
“…Some of the earlier techniques that utilised facial dynamics to analyse expressions used dynamic Bayesian networks [20] and hidden Markov models [21]. For the given input neutral and emotional images, Mlakar and Potocnik [22] computed histogram of oriented gradient based feature descriptors characterizing the differences between the two input frames. Wehrle et al [23] observed in their experiments that in a video clip advancing from neutral to emotional, the reference state of the subject was known and concluded that dynamic methods employing temporal information led to a better perception of facial expressions.…”
Section: Methods For Analysis Of the Described Features: Dynamic And mentioning
confidence: 99%